2016
DOI: 10.1017/s1751731115002669
|View full text |Cite
|
Sign up to set email alerts
|

Use of field data in pig genomic selection schemes: a simulation study

Abstract: The aim of this study was to test how genetic gain for a trait not measured on the nucleus animals could be obtained within a genomic selection pig breeding scheme. Stochastic simulation of a pig breeding program including a breeding nucleus, a multiplier to produce and disseminate semen and a production tier where phenotypes were recorded was performed to test (1) the effect of obtaining phenotypic records from offspring of nucleus animals, (2) the effect of genotyping production animals with records for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Moreover, some important traits, like disease resistance, cannot be measured in nucleus lines (Ib añez-Escriche et al 2009). By simulating a population structure organised in three tiers (nucleus, multiplier and production tiers), Lillehammer et al (2015) evaluated that the increase in the genetic gain of a trait not measured in the nucleus strongly depends on the economic weight assigned to it and that the most effective strategy, for the enlargement and update of the reference population, is the genotyping of animals of the production progeny of genotyped nucleus sires, other than the only genotyping nucleus sires. Finally, genomic prediction is calculated by using realised relationships instead of the expected genetic relationships as it happens in traditional models.…”
Section: Genomic Selection In Crossbred and Multi-breed Populationsmentioning
confidence: 99%
“…Moreover, some important traits, like disease resistance, cannot be measured in nucleus lines (Ib añez-Escriche et al 2009). By simulating a population structure organised in three tiers (nucleus, multiplier and production tiers), Lillehammer et al (2015) evaluated that the increase in the genetic gain of a trait not measured in the nucleus strongly depends on the economic weight assigned to it and that the most effective strategy, for the enlargement and update of the reference population, is the genotyping of animals of the production progeny of genotyped nucleus sires, other than the only genotyping nucleus sires. Finally, genomic prediction is calculated by using realised relationships instead of the expected genetic relationships as it happens in traditional models.…”
Section: Genomic Selection In Crossbred and Multi-breed Populationsmentioning
confidence: 99%
“…A major concern in sustainable breeding and conservation programs is the preservation of genetic variance in the population [14]. To estimate the development of genetic variance under various conditions, Monte Carlo simulations have been widely applied in animal breeding and conservation genetics since computers were introduced [5, 6], and they remain a valuable tool [7, 8]. Currently, two main types of genetic models are used to investigate developments in genetic variance via simulations: Fisher’s infinitesimal model [9, 10] and the finite locus models [11, 12].…”
Section: Introductionmentioning
confidence: 99%
“…Some reports have shown that reference population size has a significant effect on the accuracy of GEBV ( 18 , 27 ). Five reference population sizes (500, 1,000, 1,500, 2,000, 3,000) and one validation population size 1,000 were selected to perform genomic selection in this study.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, this study illustrated that the reference population including bulls that have more progeny can increase GEBV predicted accuracy ( 17 ). Lillehammer et al used simulated data to perform genomic selection of maternal traits in pigs, which illustrated that the genetic progress obtained by the population size of 1,000 was found to be 75% of the genetic progress of 5,000 ( 18 ). Anna Wolc et al used simulated data to perform genomic selection of laying chickens, and found that the generation interval was shortened by half ( 19 ).…”
Section: Introductionmentioning
confidence: 99%